Kriteria Buku Referensi Media Pembelajaran Matematika Yang Diperlukan Bagi Guru-Guru SMP Di Mataram - Sripatmi, Sripatmi; Azmi, Syahrul; Junaidi, Junaidi; Wulandari, Nourma Pramestie; lu'luilmaknun, Ulfa (Mandalika Mathematics and Educations Journal, 2021)
The purpose of this study was to determine the criteria for a mathematics learning media reference book that is needed for junior high school mathematics teachers in the city of Mataram. The research begins with a survey on whether learning mathematics requires media, then identifies the frequency with which teachers use media in learning mathematics, as well as the reasons teachers never or rarely use media in learning mathematics. Based on the survey, it was found that teachers need reference books to develop mathematics learning media, so it is necessary to develop the criteria for the required reference books. Furthermore, a literature review was conducted to compare the needs (ideal conditions) for Learning Media reference books with the current state (real conditions). Conclusion The results of the study show that the materials that require media are: arithmetic operations Integers and fractions, Linear Equations, Sets and Venn Diagrams, geometry, Function values, function graph sketches, slopes of lines, Pythagoras, circles, tangents, inner circles and the outer circle of a triangle, the properties of geometric figures, similarity, congruence, cylinders, cones, and spheres. In addition, the media needed are Concept Maps, Informative Power Points, Interactive Power Points, Student Worksheets, Learning Videos, Teaching Aids, and GeoGebra. Furthermore, the criteria for a valid book were developed based on the results of the study which included 4 aspects, namely material aspects, language, presentation of material, and graphics